Financial insecurity and mental well-being: experiences of parents amid the lebanese economic crisis - Ramona Nasr; Nada Nasr; Chadia Haddad; Samantha Abi Saab; Sara Abou Ibrahim; Joanne Karam; Abir Abdel Rahman (BMC, 2024)
Abstract Background This study investigates the impact of financial insecurity on the mental well-being and stress levels of parents in Lebanon amid the country's severe economic crisis. The context of Lebanon's economic collapse, coupled with the effects of the COVID-19 pandemic and the Beirut port explosion, has exacerbated financial and psychological distress among the population. This research aims to understand the correlation between financial instability and parental stress, identifying key factors contributing to mental health challenges in this demographic. Methods Employing a quantitative research approach, data was collected through an online survey from 785 parents from different backgrounds in Lebanon. The survey incorporated sociodemographic questions, the InCharge Financial Distress/Financial Well-Being Scale (IFDFW), and the Arabic version of the Parental Stress Scale (PSS). Data analysis was conducted using SPSS version 25. Results Findings showed significant correlations between high levels of parental stress and factors such as age (r = 0.071, p = 0.047) and lower education levels. Notably, refugees residing in Lebanon exhibited higher stress levels compared to Lebanese parents (mean stress score: 51.73 vs. 45.71, p < 0.001). Similarly, employed participants exhibited higher stress levels compared to the nonworking (mean stress score: 46.75 vs. 44.60, p = 0.003). A significant inverse association was found between financial well-being and parental stress (r=-0.216, p < 0.001), emphasizing the profound impact of economic instability on mental health. Conclusions This study highlights the adverse effects of financial insecurity on parents' mental health, primarily during a period of economic instability, emphasizing the urgent need for targeted support interventions. These findings contribute to the literature on economic crises and mental health, providing a basis for future research and policy development in similar contexts.